Characterization of cubic AgSbS2nanostructured flowers synthesized by microwave-assisted refluxing method - Narongrit Tipcompor (2018)
Cubic AgSbS2nanostructured flowers of nanorods were successfully synthesized by microwave-assisted refluxing of AgNO3, Sb(CH3COO)3, and L-cysteine (C3H7NO2S) dissolved in ethylene glycol at the pH of 4, characterized by X-ray diffraction (XRD) and electron microscopy (EM). The 1.89 eV direct energy gap was determined by UV-visible absorption, including two 688 and 857 nm emission wavelengths by photoluminescence (PL) spectroscopy. A possible formation mechanism of AgSbS2nanostructured flowers was also proposed according to the experimental results. © 2013 Narongrit Tipcompor et al.